Adherence of Primary Care Dentists to Infection Prevention and Control Guidelines at Oral Health Services in Semarang City - Sri Widuri Retnoningrum Utami Jatiputri; Ayun Sriatmi; Henry Setyawan Susanto (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Primary care dentists are the first destination for patients having dental and oral health problems. The primary dental health service also functions as a referral filter to advanced health facilities. Implementation of Infection Prevention and Control (IPC) in primary health care facilities has not been optimal, such as surveillance is not running well, data on infection incidence in primary health care has not been collected, and there is no supervision. This study aims to analyze the adherence of primary care dentists to the Infection Prevention and Control Guidelines at dental and oral health services. The research design was descriptive-analytic research with quantitative methods based on a cross-sectional study. Data collection was conducted from November to December 2022. The sampling technique used purposive sampling with a total sample of 102 primary care dentists who had been collected from a total population of 147 primary care dentists in Semarang City. The research was conducted by filling out a closed questionnaire. Data were analyzed by Chi-Square test and logistic regression test. There were significant relationships between perception (p=0.019), attitude (p=0.000), organizational support (p=0.011), clinic owner support (p=0.004), and dental facilities and health infrastructure (p=0.000) with adherence of primary care dentists to the Infection Prevention and Control Guidelines, whereas knowledge (p=0.748) had no relationship with the adherence of primary care dentists to the Infection Prevention and Control Guidelines. It concludes that primary care dentists in Semarang City have good adherence to Infection Prevention Control Guideline but that guidelines have not been implemented optimally. Keywords: Adherence Dentist, Healthcare-Associated Infections, Infection Control